Roberto Sanesi’s The First Day of Spring. An Act of Love for Humanity - Riccobono, Rossella (Incontri. Rivista europea di studi italiani, 2015)
Review of: Roberto Sanesi, The First Day of Spring. Il primo giorno di primavera, Matteo Brera (ed.), Heather Scott (trans.), Leicester, Troubador, 2014, xv + 137 p. ISBN: 9781783063772, £ 9.95.